Gold(I) Complexes with a Quinazoline Carboxamide Alkynyl Ligand: Synthesis, Cytotoxicity, and Mechanistic Studies. Issue 20 (11th May 2021) - Tabrizi, Leila; Yang, Won Seok; Chintha, Chetan; Morrison, Liam; Samali, Afshin; Ramos, Joe W.; Erxleben, Andrea
Abstract: A series of gold(I) complexes with the general formula [Au(L2 )(L′ )] (L2 =4‐phenyl‐ N ‐(prop‐2‐yn‐1‐yl)quinazoline‐2‐carboxamide, L′ =PPh3 (triphenylphosphine), 1 ; TPA (1, 3, 5‐triaza‐7‐phosphaadamantane), 2, and Me2 ‐imy (1, 3‐dimethylimidazol‐2‐ylidene), 3 ) were synthesized and fully characterized by spectroscopic methods. The alkynyl ligand L2 belongs to the quinazoline carboxamide class of ligands that are known to bind to the translocator protein (TSPO) at the outer mitochondrial membrane. 1 and 2 exert cytotoxic effects in bladder cancer cells with IC50 values in the low micromolar range. Further mechanistic analysis indicated that the two complexes both act by inducing reactive oxygen species and caspase‐mediated apoptosis. The complexes inhibit thioredoxin reductase, an established target of anticancer gold(I) complexes. Docking studies confirmed that after ligand exchange the free ligand L2 can interact with the TSPO binding site. Abstract : Alkynyl gold(I) complexes with phosphane and NHC co‐ligands have been prepared that are potent inhibitors of thioredoxin reductase. The complexes containing phosphane co‐ligands are also potent cytotoxins that reduce cell viability by inducing reactive oxygen species and caspase‐dependent apoptotic cell death.